Purkinje cell stripes and long-term depression at the parallel fiber-Purkinje cell synapse - Hawkes, Richard (Frontiers in Systems Neuroscience, 2014)
The cerebellar cortex comprises a stereotyped array of transverse zones and parasagittal stripes, built around multiple Purkinje cell subtypes, which is highly conserved across birds and mammals. This architecture is revealed in the restricted expression patterns of numerous molecules, in the terminal fields of the afferent projections, in the distribution of interneurons, and in the functional organization. This review provides an overview of cerebellar architecture with an emphasis on recent attempts to relate molecular architecture to function – in particular, the expression of long-term depression at the parallel fiber-Purkinje cell synapse.